Evaluation of the carryover effect of antibiotic, bee pollen and propolis on growth performance, carcass traits and splenic and hepatic histology of growing rabbits. Issue 3 (3rd February 2019) - Attia, Youssef A.; Bovera, Fulvia; Abd‐Elhamid, Abd El-Hamid E.; Calabrò, Serena; Mandour, Mohamed A.; Al‐Harthi, Mohammed A.; Hassan, Sabar S.
Abstract: Sixty‐four nulliparous female rabbits were distributed among eight groups (eight animals/group). Group one was the unsupplemented control group; the other seven groups were supplemented with zinc bacitracin (ZnB) at 100 mg, or bee pollen (BP) and/or propolis (Pro) at 150 and 300 mg in a capsulated form, three times a week, day after day, continuously all over the experimental period. The experiment was run for eight parties; at each parity, 28 kids of each doe group (a total of 224 rabbits) were divided into two subgroups weaned, respectively, at 24 and 30 days of age. Thus, for each parity, there were 16 groups (eight does treatments × two weaning age, 14 rabbits per group). The growing rabbits fed the standard diets without supplements. The growth performance, the carcass traits, the liver and the spleen histology of rabbits were checked up to 90 days of age to find possible carryover effects of the supplements. The supplements had no significant effect on most of the growth performance at 90 days of age, but BP150 and BP+Pro300 increased the growth rate in comparison with ZnB group. The liver weight in the control, BP300 and Pro300 groups was higher than the ZnB one. The spleen weight was higher in the groups ZnB, BP150, Pro300 and BP+Pro300, followed by the control, BP300 and BP+Pro150 and thus Pro150. The heart % in the BP150 and Pro300 groups was higher than ZnB and BP+Pro150 groups. A lymphoid hyperplasia of splenic white pulp was observed in the BP+Pro groups, while propolis alone showed a mild activation of lymphobiosis. The Pro and BP groups showed the same picture of the control group exhibiting a hydropic degeneration of mostly hepatic cells, while the ZnB group exhibited adverse effect on the bile ducts featuring portal periductal inflammatory cells infiltration with epithelial hyperplasia reflecting chronic cholangitis.